An Organizational Theory of Corporate Law - Aguirre, Emilie; Yen, Julie; Battilana, Julie (The Journal of Corporation Law, 2025)
Corporate law is in a moment of vibrant and contentious discussions about potential reforms. As firms exit Delaware, passive investment predominates, private equity expands, and public markets decline, corporate law faces a growing set of challenges that threaten its stability and efficacy. At the same time, the world faces pressing crises, including climate change, social and economic inequalities, and threats to democracy, though corporate law scholars typically consider these crises to be outside corporate law’s remit. In this Article, we argue that to understand and address the multidimensional crises that face both corporate law and society, we must address shortcomings in corporate law doctrine. We show how modern corporate law, shaped by neoclassical economic theories, provides an incomplete picture of the firm, and we propose an expanded theoretical perspective that draws from organization theory, a field long dedicated to understanding the complexities of the firm. This updated perspective demonstrates how firms actually consist of multiple constituents, including workers, the environment, and shareholders, who invest different forms of capital in the firm: labor capital, natural capital, and financial capital. It further shows that modern corporate law entrenches problematic power imbalances, privileging boards and insider shareholders over workers, the environment, and minority shareholders. Moreover, building on organization theory, we explain how corporate law fundamentally shapes and constrains firm behavior, leading these entrenched power imbalances to generate far-reaching negative consequences. To address these shortcomings, we propose redesigning board representation, fiduciary duties, and executive compensation to empower workers, the environment, and minority shareholders in relation to boards and insider shareholders. Integrating the organizational and economic perspectives can help address problematic power imbalances and ultimately provide a more effective corporate law framework to govern firms and serve society.

Who can become a Member of a Company under OHADA Law: A Critical Appraisal - Eposi, Gladys Nku Tiku (International Journal of Science and Research, 2025)
OHADA Law plays a crucial role in fostering economic growth and regional integration by harmonizing business regulations in the era of globalization and trade liberalization. This study examines the legal framework surrounding company membership under OHADA Law. While certain individuals such as legally incapacitated persons or those facing legal prohibitions cannot become company members, the law provides alternative solutions. The study explores the distinction between members and shareholders and clarifies the eligibility criteria for company membership. Using an analytical approach, this research finds that any natural or corporate entity, unless restricted by legal incapacity, prohibition, or incompatibility, can be a company member under OHADA Uniform Act. Furthermore, the law offers flexibility for incapacitated individuals by allowing legal representatives to act on their behalf.
Keywords: Business law; Company membership; Corporate governance; OHADA Law; Shareholder rights

Whistleblowers and their role in the fight against corruption. Problems in protecting whistleblowers and suggestions for improvement - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
Whistleblower protection is necessary to reduce mismanagement in private and public organisations worldwide. The protection of whistleblowers is a complex and particularly challenging task that it is up to national authorities. The research methodology is the literature review. In this context, reputable scientific journals, reports from international organisations and websites dealing with the research field of whistleblowers are studied. The main conclusions are that there is an institutional framework for the functioning and protection of whistleblowers, but best practices are not fully implemented. Furthermore, the effectiveness of the use of whistleblowers is extremely high in detecting fraud and high public risks compared to other audit techniques. For this reason, the protection and framework of the whistleblower process is increasingly being legislated for by more and more countries as their importance is recognised. Finally, monitoring the use of whistleblowers and applying best practices and criteria for their effectiveness will make their use more effective.
Keywords: Corruption; Criminal activities; Financial Crime; Fraud; Whistleblower

The Limits of Shareholder Ratification - Anabtawi, Iman (The Journal of Corporation Law, 2025)
In this Article, I analyze the expanding common law doctrine of shareholder ratification, whereby shareholder approval can, for all practical purposes, absolve directors of fiduciary liability for their conflicted business decisions. Delaware law now allows a shareholder vote to perform substantially more work than ever before. Under prevailing doctrine, in transactions between a company and any party other than a controlling shareholder, shareholder ratification reinstates the business judgment rule and makes it irrebuttable, other than for waste. Substantive judicial review is effectively avoided for such transactions. Despite its extraordinary importance in corporate governance, the shareholder ratification doctrine’s foundations are feeble and its limits uncertain. Theoretically, there is no well-established basis for equating shareholder approval with either the informed, disinterested, and good-faith decision of a board or judicial review. Doctrinally, shareholder ratification’s expansion beyond its traditional context of self-dealing has been a judicial innovation, rather than an elaboration of precedent. And historically, the shareholder ratification doctrine, which originated in early 20th-century state interesteddirector statutes, was motivated by fairness principles that were lost in translation into the common law. This Article recovers the fairness genealogy of the shareholder ratification doctrine and, in doing so, provides useful guidance for the doctrine’s development, limits, and future application.

Corporate purpose and governance in Africa: French-influenced OHADA law, local norms, and heterodox pluralism - Minzoto, Bonheur (Journal of Corporate Law Studies, 2025)
This article examines corporate governance in Africa and its significance for corporate repurposing. It relies on the framework of the Organisation for the Harmonisation of Business Law in Africa (OHADA), which unites seventeen African states under one corporate law jurisdiction while exploring how the interpretation and practice of this legal system can be integrated with or influenced by national sectoral laws and cultural norms. The workings of these different legal sources denote the case for heterodox pluralism of corporate purpose, whereby corporate membership is not tethered to shareholding only, but the workforce and neighbouring too and corporate legitimacy is not merely a function of legal arrangements but equally derives from broader society. The governance of corporations in Africa must correspond to such imperatives to ensure that the prevailing shareholder primacy norm does not continue its unencumbered de facto reign and reduce African stakeholderism to comparative impotence and mere scholarly exercise.
Keywords: CSR; Corporate governance; Corporate purpose; DRC mining legislation; Directors’ liability; Directors’ sustainability duties; Local cultures

The interpretation of social relations in the environmental, social and governance framework - Nxumalo, Nyiko (North-West University, 2025)
Environmental, social and governance (ESG) issues have gained prominence in recent years. Companies have come to understand their role in the global economy and that their decisions cannot be based solely on profits. They are now required to have regard for the environment in which they operate, to be mindful of the social factors that affect their employees, customers and the community at large, and to ensure that their corporate governance complies with the standards set out in the Companies Act 71 of 2008 and the various King Reports. While ESG has become a buzz word in the corporate world, there is still much uncertainty among stakeholders about what they are required to do and what the reporting requirements, if any, are. Its implementation in South Africa is still in its infancy and there is much uncertainty about what ESG monitoring and compliance truly entail. A perfect illustration of this is the fact that the Johannesburg Stock Exchange (JSE) only published ESG disclosure guidelines for the first time in 2022. This means that until the guidelines were published, hundreds of companies in South Africa had been wondering aimlessly in the dark when it comes to ESG issues. To make matters worse, while environmental issues and corporate governance issues have received significant attention from scholars and legislators in South Africa alike, the "S" in ESG has received little attention. It is often treated as the undesirable stepchild that everyone conveniently forgets is part of the ESG family. The purpose of this study is to highlight the gaps in the existing ESG regulatory framework, which leads to gaps in the understanding and monitoring of the implementation of the social indicators of ESG. The study aims to firstly determine whether companies in South Africa have a proper understanding of the social framework of ESG and whether the current legal and/or regulatory framework in South Africa offers sufficient guidance to n organisations to ensure that they comply with and fully implement the social guidelines of the ESG framework.
Keywords: ESG; ESG Framework; Governance factors; King IV report; Section 29 of Companies Act; Social factors; Social indicators

Editorial: Special Edition on Banking, Competition & Corporate Law: Confronting Contemporary Challenges of Banking, Competition & Corporate Law to Enhance Consumer Protection - Chitimira, Howard (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Banking; Competition; Financial crimes; Financial markets; Securities

Theories on the nature and purpose of the company and their implications for corporate governance - Ramalho, Anna Francina (University of Pretoria, 2024)
Despite the emergence of corporate governance as a formal discipline more than thirty years ago, the proliferation internationally of scholarly work on the topic and its formal regulation over this period, the scope, definition and direction of corporate governance remain contested. Company theories could potentially assist in this regard but have been inconsistent in their explanations of the both the means and ends of corporate governance. This has led to scepticism about the efficacy of theories to illuminate the phenomena associated with companies and company law. Notwithstanding, theory is critical as it makes explicit what is implicit in policymaking by regulators, as well as in the behaviour and decision-making by corporate actors, so that regulation and decisions are transparent for analysis and evaluation. The study, therefore, set out to provide a synthesis and doctrinal analysis of the main theories on the nature and general purpose of corporations in historical context. It was found that objections can be raised against all of these theories to a greater or lesser extent for inaccurate portrayal of the law, limited explanatory power and detachment from the real word. This study shows that corporate theories are a product of the settings in which they have developed and consequently none of these theories represents a universal or absolute truth, nor are they an inevitability due to widespread adoption and use. This leaves room for new formulations of the corporate form and its purpose fit for today’s context with its political, social and environmental challenges. This dissertation also includes further directions for theoretical exploration.
Keywords: Contractarianism; Corporate governance; Entity theories; Shareholder primacy; Stakeholder theories

Selected problem areas pertaining to the removal of directors from office - Shange, Thandokuhle Wandile (University of Pretoria, 2024)
This paper constitutes a composite analysis of the legal framework and procedures for removing directors and the key challenges presented by the framework. It achieves this by looking at four legal questions: Firstly, it looks into what is the legal framework for director removal in South Africa, secondly, it delves into the challenges and/or uncertainties presented by this process, and further explores if there are any possible learnings South Africa can learn from foreign jurisdiction.
Keywords: Companies Act 2008; Comparative company law; Director removal; Director’s right; Judicial review; Section 71

A comparative appraisal of creditor protection mechanisms under South African company law - Sibanda, Mandhlaenkosi (University of South Africa, 2024)
The study comparatively scrutinised creditor protection mechanisms entrenched in South African Corporate law to determine their effectiveness in advancing creditor interests in company affairs. The enquiry was triggered by the need for corporate laws to adapt to and align with the pace of global economic changes in open and democratic societies. The 2004 DTI Policy document on South African Corporate Law Reform (SACLR) proposed a shift from the traditional shareholder-centric view, which espouses shareholder importance in corporate governance, to a model that retains the supremacy of shareholder interests while simultaneously catering to the interests of other stakeholders (the enlightened shareholder value approach). In light of the DTI policy proposal, the parliament, in enacting the South African Companies Act 71 of 2008 (the Companies Act), reflected on the need to provide appropriate redress to investors' and third parties (creditors`) rights in the preamble to this piece of legislation. It was based on the forgoing expositions that this research work sought to establish whether the South African Corporate law had been adequately modelled to protect creditors and to look beyond the traditional company’s goal of profit maximisation for the shareholder at the expense of other stakeholders, such as the creditors, who equally have stakes in the success and continuation of the company. Thus, a comparative doctrinal and critical analysis of creditor protection laws from selected cognate jurisdictions was undertaken to determine the efficacy of the protection mechanisms accorded to creditors under the South African corporate jurisprudence. It is thus the researcher's findings that the South African provisions on mechanisms to protect creditors are set in motion and are, therefore, effective to a greater extent, subject to legislature dealing with some discrepancies as per lessons drawn from comparator jurisdictions and recommendations. Conclusively, the Companies Act should clearly include the creditor’s interests in those of the company and thus give a secondary duty to directors to ensure creditor interests, among other non-member stakeholders, are assertively safeguarded.
Keywords: Company controllers; Company law; Corporate entity; Corporate law; Corporate veil; Credit systems; Creditor interests; Creditor protection mechanisms; Creditors; Directors; Employees; Investors; Shareholders; Stakeholder constituencies; Stakeholder interests; Stakeholders; Third parties

Internationalisation patterns of African sharing economy companies: The role of gateway markets - Ochieng, Irene Achieng; Thornton, Heidi Coral; Owusu, Richard Afriyie (Journal of Business Research, 2024)
Sharing economy companies (sharecoms) have been internationalising rapidly, including entering African markets. Little research has been conducted on the strategies and behaviours of African sharecoms. Questions have been raised as to whether existing theories adequately explain the internationalisation of African firms. Thus, we analyse the internationalisation patterns of six African sharecoms, focusing on time, speed, and scope. The findings indicate that firms apply unique combinations of various internationalisation models. A novel pattern of internationalisation where the firms use “foreign gateway markets” as strategic “launchpads” before rapidly internationalising was also uncovered. Locational advantages, strategic networks, and relative technological advancement characterise the foreign gateway markets. We also propose the concept of “complex regional context” to define the context of emerging regions with many neighbouring countries with the potential for high levels of internationalisation but low levels of international business due to the lack of common enabling frameworks and institutions.
Keywords: Emerging African markets; Foreign gateway markets; Internationalisation; Patterns; Sharing economy

Corporate Data Responsibility - Sarfaty, Galit A. (Big Data and Armed Conflict: Legal Issues Above and Below the Armed Conflict Threshold, 2023)
This is an accepted manuscript of a book chapter in the edited volume: Big Data and Armed Conflict: Legal Issues Above and Below the Armed Conflict Threshold
This file is under embargo and will become available on 2024-12-14

An analysis of merger and amalgamation transactions under the Companies Act 71 of 2008 and the Income Tax Act 58 of 1962 - Meyer, Carolina (University of Pretoria, 2023)
In law it is common to encounter two separate pieces of legislation which govern a single matter or transaction, for example, the Companies Act 71 of 2008 (the Companies Act) and the Securities Transfer Act 25 of 2007 both of which address the sale of shares. Similarly, the Income Tax Act 58 of 1962 (the Income Tax Act) and the Companies Act both have regulations which govern, respectively, tax law and company law matters in South Africa. These two Acts overlap in various business and commercial fields as tax is frequently an important component of any business transaction undertaken by a company. Issues, however, arise when the regulations in these two Acts, are inconsistent. This can be observed if one compares the current South African Income Tax and Companies Act, specifically as regards the sections involving merger and amalgamation transactions. Section 44 of the Income Tax Act governs merger and amalgamation transactions from a tax perspective and provides for tax rollover relief if certain requirements are met. The regulations governing mergers and amalgamations under the Companies Act are contained in sections 113, 115 and 116 of the Act. Although these sections in both Acts address the same transaction – a merger or amalgamation between two or more companies – there are several discrepancies between the regulations in the two Acts which appear to operate entirely independently of one another. In practice, one often sees that other sections in the Companies Act and Income Tax Act are used to achieve a merger due, in the main, to the uncertainties in the application of the relevant merger sections in the two Acts and the limited interaction between them. This study identifies and assesses the impact of the discrepancies identified in these two Acts in relation to merger and amalgamation transactions. The study makes recommendations to address these discrepancies and to align the South African Companies Act and Income Tax Act as regards merger/amalgamation transactions.
URI: https://repository.up.ac.za/handle/2263/94064
Keywords: Amalgamation; Companies Act; Income Tax Act; Merger; Taxation

Liability in the atmosphere of groups of companies - Motassim, Sofia (Universitat de Barcelona, 2023)
Groups of companies are a complex corporate structure, whose regulation can be problematic, especially when it comes to liability. Indeed, liability within corporate groups draws forth a series of issues principally due to the principles of separate corporate personality and limited liability. In the context of limited liability, which is based on the notion of separate legal personality, the main issue waxes the protection of the creditors, in particular the creditors of the subsidiaries. One can find three regulatory templates for handling corporate groups and their liability: policing via general company and/or civil law (such as the English model); policing via special group legislation (such as the German model); and policing via branches of law such as insolvency law, antitrust law, and contract law, among others (which is the case in numerous jurisdictions, either coupled with the first or the second model). Lifting the corporate veil has come as an answer to corporate separateness, by permitting to ignore the shareholders’ limited liability and hold them personally liable for the debts of their companies in specific circumstances. However, one can hardly find cases in which the corporate veil has been successfully lifted, due to many factors. Other important questions that are posed in the scope of corporate groups liability are the parent company’s liability for the payment of its daughter companies’ debts when insolvency strikes and other respects, besides the matter of group liability. Furthermore, liability is as well a key player in terms of tort law, and corporate social responsibility has therefore found a place in the sun in the present climate.
Alternate link : https://diposit.ub.edu/bitstreams/83cde66e-b943-45b6-830b-831df41cb73f/download
Keywords: Ciències Jurídiques; Commercial law; Conglomerate corporations; Corporations; Derecho mercantil; Dret mercantil; Econòmiques i Socials; Grupos de empresas; Grups d'empreses; Liability (Law); Responsabilidad (Derecho); Responsabilitat (Dret); Sociedades; Societats

Mandatory Environmental, Social and Governance (ESG) Regulations: ESG Performance, Corporate Finance, and Investment - Michael, Emmanuel (Victoria University of Wellington, 2023)
This thesis investigates the relationship between cross-country mandatory environmental, social and governance (ESG) regulations and firm-level outcomes, such as ESG performance, corporate finance, and investment, for both developing and developed countries. ESG performance is initially examined to determine whether mandatory ESG regulations affect it and to what extent. Second, the study investigates the impact of mandatory ESG on corporate finance and investment. Lastly, the study explores whether mandatory ESG regulations affect firm-level outcomes based on countries' governance and economic systems, and industries. The study uses a large sample of 69,010 firm-years across 73 countries, over the period 2005 – 2020 to address the foregoing issues. In addressing the impact of mandatory ESG regulations on ESG performance, the study employs a difference-in-differences (DiD) design. The DiD technique can isolate the effect of regulatory shocks to firm-level outcomes. According to the DiD analysis conducted, cross-country mandatory ESG improves firm-level ESG performance in developed countries, but not in developing countries. The study also concludes that mandatory ESG regulations have a positive impact only on ESG components in developed countries and have a more dominant impact on environmental (E) component. The findings are robust to a range of checks and test cases, including a triple DiD design set-up and propensity score-matched sample. The study employs an investment Euler equation framework and generalised method of moments (GMM) estimators to explore how mandatory ESG impacts corporate finance and investment. Euler frameworks account for the dynamic nature of investment, whereas GMMs account for endogenous dynamics in dynamic models. The study demonstrates that mandatory ESG increases corporate investment by increasing firms' access to external funds. The findings are robust to a battery of tests, including a triple DiD design set-up, propensity score-matched sample and the parallel trends assumption. Using an investment Euler equation framework and the GMM estimators, the study explores whether the impact of mandatory ESG on corporate finance and investment is dependent on a country's governance and economic system. When mandatory ESG is affected by country factors such as governance systems and economic well-being, the effect of mandatory ESG on investment via internal finance channel persists, according to the study. However, while consistent results are found in developed countries, inconsistent results are found in developing countries. According to the study, oil, gas, and mining firms are likely to respond effectively to mandatory ESG regulations because of increased scrutiny and pressure. Overall, the findings from the study imply that cross-country mandatory ESG has had a positive impact on corporate ESG performance, finance, and investment. For firms located in developed countries, these findings hold consistently, while for those located in developing countries, the opposite holds true. Also, the study reveals that firms in the oil, gas, and mining industries effectively respond to regulatory requirements. As a result, this study provides policy makers and accountants with an understanding of how mandatory ESG impacts firm ESG activities and performance, which is crucial for regulatory reforms.
Keywords: Corporate Finance; Cross-Sectional Analysis; Developed countries; Developing countries; Economic Models and Forecasting; Finance; Financial Economics; Investment; Investment Euler equation; Mandatory ESG disclosure regulations; Panel Data Analysis; Sustainability Accounting and Reporting; Time-Series Analysis

Who Are the Best Law Firms? Rankings from IPO Performance - Bates, Thomas W.; Lv, Jin Roc; Neyland, Jordan (The Journal of Corporation Law, 2023)
Recent scandals have brought rankings to the forefront of the legal profession. Several of the most prestigious academic institutions have withdrawn from being ranked, citing the problematic nature of the rankings. However, rankings persist for both legal academics and practice, and there is substantial sentiment to improve the methodologies, with little detail as to how to improve. In this paper, we rank law firms on their clients’ IPO performance. We focus on the most relevant outcomes: litigation, first-day returns, disclosure, and legal fees. The focus on these measures provides benefits relative to other methodologies, which typically focus on inputs or size-related characteristics. Namely, this ranking is less manipulable and more accurately captures performance metrics that matter most to clients’ shareholders. Our rankings control for observable and unobservable deal characteristics, which helps ensure we capture law firm quality, not client traits. With the rankings based on legal fees, potential clients can compare the benefits of a particular law firm (e.g., lower litigation or higher selling prices) against the additional cost of hiring a higher-quality law firm. Hence, our rankings allow for a value-for-the-money comparison of law firms for clients selling shares in an IPO.
Keywords: Disclosure; IPO; Lawyers; Litigation; Rankings; Securities Regulation

The Double Life of State-Owned Enterprises in International Economic Law: States, Corporations or Both? - Kikarea, Eirini (University of Cambridge, 2023)
State-owned enterprises (SOEs) have recently gained prominence in global markets and feature among the world’s most influential enterprises. The aim of this research project is to analyse the international norms in force regulating whether SOEs are considered state or non- state actors, and their conduct state or non-state conduct, the interpretation and application of these norms by adjudicators in different international regimes, and to provide alternative prisms through which these rules and decisions can be assessed and re-thought by political actors. I show that, in relation to SOEs, the concepts ‘state and ‘act of state’ have been ascribed diverse meanings by adjudicators and other international actors, who have employed legal standards with divergent wording and thresholds when dealing with similar questions. I argue that the fragmented meaning of these terms should be understood, in part, as a result of the inherent malleability of these terms and the different expert vocabularies employed across regimes. It is exhibited that adjudicators in the international trade and investment regimes are more inclined towards piercing the corporate veil of SOEs, potentially evidencing the existence of biases against SOEs, which are perceived as inherently economically inefficient and politically motivated actors in an indiscriminatory manner. In the last chapter, I introduce alternative lines of thought regarding the regulation of SOEs in international law. I suggest that, instead of engaging in theoretical discussions on the proper delineation between the public and the private sector, it is more useful to focus on the distributional impact of international rules on various actors, especially on developing and emerging economies where the presence of SOEs is very high. Such alternative prisms of analysis open paths for future research and practice, with the goal of designing an international economic order that incentivises institutional experimentation in the pursuit of economic development and distributional equity.
Keywords: International Economic Law; International Investment Law; International law; International trade law; Public enterprises; State capitalism; State-owned enterprises

The regulation of Corporate phoenix activity in South Africa - Basson, André Stephan (University of Johannesburg, 2023)
Phoenix activity involves conduct whereby a failing company (the old company) is replaced by a second company (the new company) in the operation of the same or a similar business and that involves the same or similar company controllers. Transactions of this nature can be legal and even be beneficial to society, since entrepreneurs who pursue a viable business may, if the new company succeeds, benefit the economy and many other stakeholders. These transactions are referred to as legal phoenix activity. Problems arise however when phoenix activity is engaged in with the goal of evading the debt of the old company, known as illegal phoenix activity. In other cases, even well-intentioned company controllers can cause significant harm by resurrecting a fundamentally flawed business. This conduct, although not illegal, is unduly prejudicial to stakeholders and is known as problematic phoenix activity. While this thesis focuses on illegal phoenix activity, several measures identified should also curb problematic phoenix activity. This study identifies the elements and common characteristics of illegal phoenix activity. It then analyses regulation pertaining to those elements and common characteristics with the aim of finding effective solutions to the problem. This includes evaluating measures that reverse prejudicial transactions that occur during illegal phoenix activity as well as holding complicit parties, such as company controllers and the new company, accountable for their actions. Regulation aimed at preventing and investigating illegal phoenix activity is also considered. This thesis uses the comparative legal approach to analyse regulatory responses to illegal phoenix activity. Australia, the United Kingdom, and the United States of America are examined. Several reported cases in South Africa involving what appear to be illegal phoenix activity are explored, along with the existing measures that are applicable to illegal phoenix activity in South Africa. A single anti-phoenix provision is undesirable as it has the potential to unjustifiably infringe on legal phoenix activity. This thesis proposes a multi-pronged approach, which involves a combination of better enforcement of existing laws and the introduction of smaller targeted amendments to legislation aimed at reducing the incidence illegal phoenix activity.
Keywords: ABUSE OF THE CORPORATE FORM; Bankruptcy fraud; Evasion of liability; Fraud on creditors; Phoenix activity; Phoenixism; Strategic bankruptcy; Successor liability; Transactions prejudicing creditors; Transfers at an undervalue

The International Handbook of Social Enterprise Law: Benefit Corporations and Other Purpose-Driven Companies - Peter, Henry; Vargas Vasserot, Carlos; Alcalde Silva, Jaime (Springer Nature, 2023)
This open-access book brings together international experts who shed new light on the status of social enterprises, benefit corporations and other purpose-driven companies. The respective chapters take a multidisciplinary approach (combining law, philosophy, history, sociology and economics) and provide valuable insights on fostering social entrepreneurship and advancing the common good. In recent years, we have witnessed a significant shift of how business activities are conducted, mainly through the rise of social enterprises. In an effort to target social problems at their roots, social entrepreneurs create organizations that bring transformative social changes by considering, among others, ethical, social, and environmental factors. A variety of social enterprise models are emerging internationally and are proving their vitality and importance. But what does the term “social enterprise” mean? What are its roots? And how does it work in practice within the legal framework of any country? This handbook attempts to answer these questions from a theoretical, historical, and comparative perspective, bringing together 44 contributions written by 71 expert researchers and practitioners in this field. The first part provides an overview of the social enterprise movement, its evolution, and the different forms entities can take to meet global challenges, overcoming the limits of what governments and states can do. The second part focuses on the emergence of benefit corporations and the growing importance of sustainability and societal values, while also analyzing their different legal forms and adaptation to their regulatory environment. In turn, the last part presents the status quo of purpose-driven companies in 36 developed and emerging economies worldwide. This handbook offers food for thought and guidance for everyone interested in this field. It will benefit practitioners and decision-makers involved in social and community organizations, as well as in international development and, more generally speaking, social sciences and economics.
Accepted: 2023-01-20T16:54:44Z
Keywords: B-Corps; BCorp Certification; Benefit Corporations; Business and Management; Business ethics; CSR; Commercial Law; Competencia; Competition law; Corporate Social Responsibility; Finance; Social Business Inititive; Social Enterprises; Social Entrepreneurship

Corporate Governance and Women on the Board of Directors : the Legal Framework towards a Minimum Harmonisation in the European Union - Lamy Martin, Joy (Université Paris-Saclay, 2022)
This thesis concerns the recent and considerable change in corporate governance legislation, specifically how boards of directors address the issue of parity and the appointment of its members in public limited companies. This research will challenge European Union law which, to date, does not propose EU harmonization.The UK, France, Germany and Norway (a non-member country but one that will be included in this research) have introduced changes to their national legislation in relation to company boards in public listed companies. This research will focus on a comparative study of parity on company boards under European Union law and its application in the UK (pre-Brexit), Germany, France and Norway. The application of corporate governance codes or soft law and the proposal for a hard law directive demonstrate a fragmentation in the EU, as the application of law by hard quotas divides member states and parliamentarians in European Union law. Corporate governance law in the member states varies considerably, but it must respect the EU's primacy law. Comparisons of legislation between member states reveal the marked differences in law.Women are significantly under-represented on the corporate boards of public limited companies in Europe. Legitimate questions need to be asked. Does the European Commission have the right to make a proposal for a directive allowing for parity on the boards of public limited companies in the EU? The reality is that the Commission does not have a solid approach in dealing with the issue of parity. As long as there is too much inconsistency between Member States, this leaves considerable room for further research. Legislation and governance law between member EU member states diverge considerably and demonstrate inconsistency with the legislation between them, resulting in little or no consensus in the interpretation of EU law. Or member states diverge with opposing interpretations of EU law, especially concerning sovereignty.National legal systems differ considerably in the way legislation allows for the appointment of board members and the notion of parity. A review of corporate governance matters concerning shareholders, the composition and appointment of board members corporate governance codes reveal the gap between member states. The research focus on parity by way of a comparison of the soft and hard laws of the member states.. The research upholds European law Article 157(3) Treaty of the Functioning on the European Union (TFEU), which is the fundamental principle of EU law and basis of gender equality and parity.The research will contribute to raising awareness of this issue through quota legislation and the question of parity on boards in public limited companies in the EU.
Issue: 2022UPASH012
Keywords: Board of directors; Comparative Law; Conseil d'administration; Corporate Governance; Droit comparé; Gender and parity; Genre et parité; Gouvernance des entreprises; Quotas; The European Union; Union européenne

Analysis of the Determinants of the Effectiveness of the Board of Directors in Family Businesses in Cameroon - Roukatou, Aboubakar; Dretti, Denise (Open Journal of Business and Management, 2022)
The composition of the Board of Directors is commonly presented as an understandable variable for its effectiveness. However, the work that examined the relationship between the composition and effectiveness of the Board is not characterized, as they require about whether or not certain categories of directors (internal, external, independent) are relevant and the related empirical results are mixed. This work examines the relationship between the characteristics of the board of directors and its effectiveness in a type of business that is very common in the world, respecting the family business. Thus, the problem that this study tries to solve is to identify the characteristics of the board of directors that can contribute to its effectiveness in Cameroonian family businesses. We found that the size of the Board, the presence of external directors, and the cumulative management and control functions appear to have an impact on the effectiveness of the Board.
Number: 5
Keywords: Board of directors; Family Business; Governance; Public Limited Company

The Effects of Covid-19 Crisis on Good Governance at the Local Level, The Case of Tunisia - Braham, Fatma; Seguir, Sonia (Journal of the Association of Arab Universities for Research in Higher Education, 2022)
The COVID-19 crisis, in addition to its serious health impact, has negatively affected key socio-economic aggregates and has shocked the strategic planning of all economic and social actors, including local communities. In search of resilient, skillful and intelligent good territorial governance, the municipalities are working to adapt their governance systems to the new social and environmental priorities. This work proposes a new reading of the acquired approaches to good governance, a new paradigm related to the new conjuncture and an assessment of the performance system at the central and local levels

Do corporate governance codes matter in Africa? - Areneke, Geofry; Khlif, Wafa; Kimani, Danson; Soobaroyen, Teerooven (Research Handbook on Corporate Board Decision-Making, 2022)
Africa is often depicted in the literature as the ‘patron late to the party’ on account of her low uptake of corporate governance codes. Notwithstanding, countries that have an existing corporate governance code continue to exhibit weak corporate accountability and governance practices. This prompted a critical analysis based on a detailed review of published articles and existing codes in the African multiple-contexts. Our findings reveal that the efficacy of many codes remains very limited in terms of pragmatic outcomes whilst firms in countries that have adopted codes continue to face uneven performance and poor accountability. We conclude by urging for an understanding of the reasons underlying such results. We recommend an African led re-think (independence, ownership, board processes) of existing codes to make them more aligned with the governance needs of African firms and their complex sociocultural background. We call for further research to illuminate Africa’s actual governance experiences and necessities.
Keywords: Africa; African principles; Board of directors; Boardroom processes; Codes; Corporate governance; Developing countries; Neo-colonialism

La publication des informations sociétales suivant les lois comptables revisées OHADA - Guimezap Épse Choukem, Claire (Revue Française d'Economie et de Gestion, 2021)
Dans un contexte marqué par le développement durable, le législateur OHADA n’a eu de cesse d’être accablé de toutes parts pour son statisme vis-à-vis de la montée des problématiques sociétales. Au lendemain des reformes du système comptable OHADA, les problématiques sociétales ont une fois de plus raté le rendez-vous de la normalisation. Toutefois, de nombreuses entreprises continuent à publier leurs informations sociétales parallèlement à leur communication financière. A cet effet, le problème que soulève cet article est celui de la compréhension des modes de production et de diffusion des informations extra-financières en l’absence d’une réglementation en la matière. Une étude empirique de nature descriptive est menée auprès d’un échantillon de 120 entreprises diffusant leurs informations sociétales au sein de l’espace OHADA. Il en ressort que le site internet et l’implication dans le développement de la communauté locale sont apparue respectivement comme support et thème de diffusion les plus utilisés dans l’espace OHADA en matière de reporting sociétal sous la pression de certaines parties prenantes notamment les associations consuméristes, les départements ministériels en charge de l’environnement, du travail et de la sécurité sociale. In a context marked by a widespread awareness of the needs of sustainable development, the OHADA legislator has been constantly burdened on all sides for its statism to the rise of societal problems. However, After the reform of the OHADA system, sustainability problems once more did not met up with the appointment of normalization. However, several enterprises continue to publish their societal information in parallel with their financial communication. As such, the problem raised by this article is that of understanding the mode of production and disclosure of non-financial information in the absence of a regulatory framework. A descriptive empirical analysis is carried out with a sample of 120 enterprises which propagate their societal information in the OHADA zone. It reveals that internet websites and implication in the development of the local community are respectively the medium and theme of the most used disclosures in the OHADA zone with regards to sustainability reporting under the pressure of some stakeholders especially consumer associations, ministerial departments in charge of the environment labor and social security.
Keywords: Accounting law; CSR; Corporate Social Responsibility; Droit comptable; Information sociétale; Parties-prenantes; RSE; Responsabilité Sociétale de l'Entreprise; Stakeholders

The influence of capital structure and profitability on the solvency of nascent SMEs - Amoa-Gyarteng, Karikari (University of Johannesburg, 2021)
Even though small and medium enterprises contribute significantly to the growth of national economies, they are vulnerable in their early stages and may fail. Hence younger businesses are more likely to fail than more established ones because they face complex challenges that may limit their viability. This is a notion established in the liability of newness framework. According to the liability of newness concept, the precarious existence of emerging organisations is due to difficulties in managing relationships among strangers, not quickly assembling resources, and not coping with difficult environments, among other issues. All these elements notwithstanding, previous literature suggests that small businesses can, and sometimes do engage in techniques or approaches to help reduce the liability of newness, such as raising adequate capital. This study suggests that not only is adequate capital important but that the right mix of capital also results in higher solvency, thereby mitigating the liability of newness. Because the various funding forms have distinct advantages and disadvantages, an appropriate capital structure reduces the cost of financing while increasing the value of the firm. This study also advances the idea that profitable businesses are productive and financially strong, and thus nascent enterprises with high profitability can minimise the liability of newness. As a result, the study sought to examine the influence of capital structure and profitability on the solvency of nascent small and medium enterprises. To put the study's hypotheses to the test, 1106 nascent small and medium enterprises that are registered with the National Board for Small Scale Industries were sampled across three major cities in Ghana. Thus, data was gathered from every member of the population. Such data, gathered from the SMEs' financial statements, was submitted to preliminary screening as well as a number of statistical measurements. Operationally, the dependent variable, solvency, was defined as the solvency ratio, working capital ratio, and net worth. As a result, three distinct regression models were developed for robustness. The study's findings broadly indicate that capital structure and profitability have an influence on the solvency of nascent small and medium enterprises. The study also determined that emerging small and medium enterprises should follow the principles of the pecking order theory to reduce the liability of newness. These findings, if adopted by SME owners, can aid in the maturation of their fledgling businesses.
Keywords: Entrepreneurship; New business enterprises

The Contents of the Articles of Association as a Document used in the Creation of Companies in Cameroon under the OHADA Law - Eposi, Gladys Nku Tiku (International Journal of Science and Research, 2021)
This study unveils that the creation of companies in Cameroon is been regulated by the OHADA[1], law under the Uniform Act on Commercial Companies and Economic Interest Groups (UACCEIG) which says, every company must have its own Articles of Association [2]. The Articles of Association is a document that contains the internal regulation for the management of the company’s affairs. [3] The articles of association are the contracts between the shareholders and the company and among the shareholders themselves. [4] The questions raised are what are the requirements common in the Articles of Association of all companies under OHADA Law? What effect do the AOA has? The study adopted an analytical approach which has led to the finding that the AOA under OHADA, is similar to the MOA [5] in most English speaking countries, but a major difference in that UACCEIG has limited the life span of the company to 99years while under English company law, a company goes on for an indefinite period. [6] The life span of the company should not be limited due to the principle of perpetual succession. The UACC seem to have concurred with some aspects of the Common Law, making the UACC an applaudable law reform.
Keywords: Articles of association; Cameroon; Commercial companies; Notarised deed; OHADA Law

COVID-19 and Comparative Corporate Governance - Gelter, Martin; Puaschunder, Julia M. (The Journal of Corporation Law, 2021)
With the pandemic caused by the novel coronavirus SARS-CoV-2 raging around the world, many countries’ economies are at a crucial juncture. The COVID-19 external shock to the economy has the potential to affect corporate governance profoundly. This Article explores its possible impact on comparative corporate governance. For an economy to operate successfully, a society must first find a politically sustainable social equilibrium. In many countries, historical crises—such as the Great Depression and World War II—have resulted in a reconfiguration of corporate governance institutions that set the course for generations. While it is not yet clear whether COVID-19 will have a similar effect, it is possible that it will change patterns of what kind of firms are -from an evolutionary perspective- likely to survive, and which ones are not. We argue that to some extent, it will accelerate ongoing trends, whereas in other areas it put corporations on an entirely new course. We observe three trends, namely the need for resilience, a growth of nationalist policies in corporate law, and an increasing orientation toward “stakeholder” interests. First, firms will have to become resilient to the crisis and consequently long-term oriented. Corporations that are not operating merely on an arm’s length capital market basis but are integrated into a network, generated by core shareholders, state ownership, or bank lending may be more likely to survive. In addition, firms are beginning to interact with their workforce differently in their attempts to maintain what could be called “healthy human capital.” Second, we are likely to see a resurgence of nationalism in corporate governance to ensure that foreign ownership and interconnected supply chains do not put national security at risk. Third, the existing critiques of inequality but also climate change awareness will accelerate the trend toward a broadening of corporate purpose toward “stakeholderism” and public policy issues. As in the past years, institutional investors acting as “universal owners” will play a role in shaping this trend.
Keywords: Behavioral; COVID-19; Climate change; Corporate governance; Corporate law; Economic protectionism; Evolutionary theory; Free cash flow; Green New Deal; Human capital; Inequality; Nationalism; Ownership structure; Relational finance; Shareholder primacy; Stakeholder theory; Varieties of capitalism

An Empirical Analysis of Private Equity Investment Affecting Enterprise Value - Li, Jianhong (Université de Genève, 2020)
The lack of long-term and stable financial support for SMEs is the fundamental reason why enterprises cannot develop for a long time. At present, the situation of financing difficulties for SMEs is becoming more and more serious. Private equity (PE) investment has emerged as an important financing method. Private equity investment, while broadening the financing channels of SME capital markets, brings advanced management experience to enterprises, which helps enterprises to develop rapidly and effectively. According to the statistics of the Zero2IPO Research Center, the active investment institutions in China's equity market have grown from more than 200 in 2000 to more than 14,000 in 2018, with a total asset under management over RMB 9 trillion. Great progress has been realized in the scale and development of the industry. In addition, with the launch of the GEM in 2009, PE investment industry met new opportunities of development and became popular. At present, the development of China's PE investment business is still at an early stage. Neither relevant policies, laws and regulations nor supporting mechanisms are mature enough. Therefore, researches on China's PE investment business needs to be carried out. In this context, more and more scholars are beginning to focus on the field of PE investment. This paper focuses on whether PE investments can fundamentally increase the enterprise value. The basic theory is sorted out to serve as the theoretical basis for this study. Through a systematic analysis, this paper draws out 4paths of PE investment affecting enterprises, which are the influence on technological innovation, corporate governance activities, dividend distribution decision and earnings management, respectively. And through empirical analysis, it finds the empirical basis of the impact of PE investment on enterprise value, and investigates how PE investments affect enterprise value based on the difference in investment characteristics such as investment duration and whether the investment is joint or not. This paper conducts an empirical test by selecting the listed companies of the Shenzhen Stock Exchange GEM in 2015-2018 as sample. The results show that the investment of PE firm will significantly increase the value of the target enterprise. This paper makes a detailed analysis of sample data. The conclusion of the study is that private equity investment will have a significant impact on the value of target enterprises. Private equity investment plays an important role in the modern governance structure of small and medium-sized enterprises in China This paper enriches the existing literature and provides constructive suggestions for the health development of the PE investment market. 中小企业缺乏长期稳定的资金来源是企业无法长久发展的根本性原因，目前 中小企业融资难的形势越来越严峻，私募股权投资作为一种重要的融资手段应运 而生。私募股权投资在拓宽中小企业资本市场融资渠道的同时，给企业带来先进的 管理经验，有助于企业快速并有效的发展。据清科研究中心的统计数据显示，中国 股权市场活跃的投资机构已由 2000 年的 200 多家发展到 2018 年的 1.4 万多家，管 理资本量超过 9 万亿人民币，行业规模和发展实现了质的飞跃。此外，随着 2009 年创业板的推出，私募股权投资行业的发展业迎来了新的希望和契机，私募股权投 资业务开始盛行。目前，我国私募股权投资业务的发展还处于早期阶段，无论是从 政策还是法律法规再到配套机制，都还不够健全。因此，对我国私募股权投资业务 的研究亟需开展，在此背景下，越来越多的学者开始关注私募股权投资这一领域。 本文研究的重点是私募股权投资是否能够根本上提升企业价值。本文首先对 基础理论进行了梳理，以此作为研究的理论依据，而后论述了私募股权投资对被投 资企业价值影响的理论分析，。本文通过系统的理论分析得出了私募股权投资影响 企业的路径，并通过实证分析，得到私募股权投资对企业价值的影响的实证依据， 并且从投资期限和是否联合投资等投资特征的差异性，深入研究私募股权投资对 企业价值的影响方式。本文通过选取深圳证券交易所创业板 2015-2018 年的上市企 业作为样本，进行了实证检验，并得出以下研究结论:私募股权投资的参与会显著 提升目标企业的价值，同时，私募股权投资的期限越长、联合投资机构的数量越多， 目标企业的价值也会越高。 本文基于理论又结合实际，对样本数据进行了分析，研究的结论是私募股权投 资会对被投资企业的价值产生显著影响。私募股权投资对于我国中小企业的现代 化治理结构起到了完善作用。本文的研究结果丰富了现有文献，对私募股权投资市 场健康发展提出了建设性的建议。
Keywords: Enterprise Value; Investment Term; PE Investment

Corporate Shares as Shares - Katz, Larissa (Modern Studies in Property Law, 2019)
In this chapter, I ask whether shares in corporations ought to command more attention within theories of property. Contemporary liberal property theorists typically take land (and sometimes goods) as the basic case of property. Shares tend to be left out of these accounts or treated as imitations or mutations of the basic case. Economists, for their part, have transformed the idea of ownership: ‘owner’ refers to the ultimate beneficiary of the value of assets. Shares are treated as a central case of property by those who take this approach. Shareholders are taken to own the corporation insofar as they are the ultimate beneficiaries of its value. In this chapter, I concede shares do not fit within the traditional property framework. This does not mean, however, that the traditional idea of property is obsolete and that a new property framework is in order.
Accepted: 2023-06-22T17:00:40Z ISBN: 9781509921379 Publisher: Hart Publishing

Abuse of legal personality to avoid tax : piercing the corporate veil as remedy in case of the abuse of legal personality for tax purposes - Marais, Albertus Johannes (Stellenbosch University, 2019)
Companies are legal persons and as much part of commercial traffic as the natural persons owning and controlling them. Compared to one another, companies and natural persons nevertheless have very different legal abilities and characteristics. It is therefore not unexpected that they are treated differently for purposes of the law of taxation. As a result it may often be more beneficial to have the profits generated by a business enterprise taxed in a company rather than in the hands of a natural person, especially in instances where a shareholder would be commercially indifferent to whether those profits are generated in a company or not. By using the separate legal personality of a company shareholders may often perpetrate an abuse of that separate legal personality. Such abuse of legal personality can also take place when legal personality is employed primarily for tax reasons. While a limited form of abuse of the corporate veil is tolerated, whether the use of separate legal personality for tax reasons amounts to an abuse thereof beyond what is permitted in South Africa can be determined in terms of three tests. These tests are the traditional “piercing of the corporate veil” judgments forming part of the common law, section 20(9) of the Companies Act 71 of 2008 and the General Anti-Avoidance Rules (“GAARs”) (and other specific provisions) in the Income Tax Act 58 of 1962. This dissertation considers when any of these various tests will dictate that the separate personality of a company be ignored (or “pierced”) for purposes of taxes levied in terms of the Income Tax Act. Through critical analysis of both the South African rules on piercing as applied for tax purposes as well as the circumstances under which selected other jurisdictions provide for piercing for tax reasons the dissertation formulates what best practice and desired policy for piercing for tax reasons are.
URI: http://hdl.handle.net/10019.1/106096
Keywords: Close Corporations Act; 1984; Companies Act; 2008; Corporate veil; Corporations; Income Tax Act; 1962; South Africa; Tax evasion; Taxation; Unconscionable abuse

Regulation of takeovers and mergers with an emphasis on the mandatory offer rule: a comparative and critical analysis of the law and the institutions that have been set up to enforce the law - Phakeng, Madimetja A. L. (Stellenbosch University, 2019)
ENGLISH ABSTRACT :This dissertation assesses the regulation of takeovers and mergers and the institutions created to enforce the law, from a comparative perspective. It uses South Africa as its point of departure and takes the laws of Delaware in the United States, the United Kingdom and Australia into account. The dissertation indicates that numerous takeover provisions in South Africa are poorly formulated, making them difficult to interpret and apply. Accordingly, the dissertation recommends amendment and improvement of certain Takeover Provisions. Special emphasis is placed on the mandatory offer requirement. The dissertation critically and comparatively analyses this requirement and especially its impacts on the market for corporate control, efficient usage of capital, corporate governance and (in South Africa) Broad Based Black Economic Empowerment. It appears from the literature explored that the mandatory offer requirement originated from the Perlman case in the United States as an expression of the equal opportunity rule. According to the equal opportunity rule, the controlling stake of a company is enriched with a premium of control, which must be shared with other shareholders when there is a change of the controlling shareholder. Shareholders must be given an equal opportunity to share in this control premium. Hence, a mandatory offer must be made to the remaining shareholders of the company by the new controlling shareholder at a price at which control was bought. Perlman case was decided in the United States of America during 1955. It is contended in the dissertation, that the mandatory offer requirement in section 123 of the Companies Act 71 of 2008 (“the Act”), can ultimately be traced back to this case. Researchers have criticised the mandatory offer requirement in a number of respects. It has been pointed out that the rationale for the decision in the Perlman case was not clear and applied in limited circumstances. Other scholars point out that the case was not a final decider on the sharing of the control premium due to later judicial pronouncements that differed with that case. Despite these commentaries, it appears that the case became a basis for imposing and enforcing this most debated rule in takeover and merger law. The dissertation concludes that the sharing of a premium of control, as envisaged by the mandatory offer requirement, is not enforced in the state of Delaware. It further concludes that in the UK, the mandatory offer rule forms the cornerstone of enforcement of the equal opportunity rule, but that widely dispersed shareholding ameliorates it negative consequences in that jurisdiction. The dissertation favours the Australian approach. That jurisdiction does not require a mandatory offer similar to that in section 123 of the Act, but, Australian Takeover Provisions, unlike their South African equivalent, have been tailor-made for Australian market conditions. The dissertation accordingly concludes that the mandatory offer requirement in section 123 of the Act in its current form is not appropriate for South Africa.
URI: http://hdl.handle.net/10019.1/105995
Keywords: Consolidation of corporations; Delaware; Great Britain; Merger of corporations; Regulation; South Africa

Assessing the nexus between corporate governance, corporate social responsibility and corporate regulation: the way forward for the OHADA zone - Tambutoh, Dashaco John; Tarh, Bande Gulbert Mbah (International Journal of Advanced Research and Publications, 2018)
Encyclopaedic Corporate Governance (CG) is now a mainstream issue of concern in the business world. Yet, there has been no systematic investigation of CG practices in general, allowing for a distinction between the profit and non-profit organizations. In this regard, this article aims to investigate the nuances in the application of sound governance principles across different types of organizations in general, together with the understanding and applications of Corporate Social Responsibility (CSR) and Corporate Regulation (CR) in the context of the OHADA zone. With CSR envisages as a model of CG that extends the fiduciary duties from fulfilment of responsibilities towards the shareholders of the firm to fulfilment of analogous fiduciary duties towards all the firm?s stakeholders. Thus, after considering the place of CSR in the debate about alternative CG modes, a full-fledged social contract foundation of the multi-stakeholder and multi-fiduciary model is present. The article, therefore, shows that CSR is a social norm that would endogenously emerge from the stakeholders? social contract seen as the first move in an equilibrium selection process that reaches the equilibrium state of a CG institution; and as a global trend involving corporations, states, international organizations and civil society organizations. Besides, the article portrays the trend of CSR in three ways: as a regulatory framework that places new demands on corporations; as a mobilization of corporate actors to assist the development aid of states and; as a management trend. With each of these portraits suggesting certain actors, relations, driving forces and interests as being central. These multiple identities may partially describe the trend?s success, but could equally well describe its contestation, fragility and fluidity. Based on the argument that CSR is not just a fashion but rather the future from another angle, the article explicitly explores the nexus between CSR, CG and CR as appreciated in the OHADA zone. It also presents fresh insights into the applications of CG and CSR principles under the OHADA perspective that has not received systematic attention and consideration in the literature and, thus, provides policy recommendations to mainstream a viable CSR framework in the OHADA zone.
http://www.journalijar.com/
Keywords: Corporate Regulation; Corporate Social Responsibility; Corporate governance; OHADA

A critical analysis of the removal of directors by the board of directors and the judiciary under the Companies Act 71 of 2008 - Cassim, Rehana (University of South Africa, 2018)
Section 71(3) of the Companies Act 71 of 2008 has introduced into South African company law a provision which for the first time permits the board of directors to remove another director from office in certain specific instances. A further significant innovation in the Companies Act 71 of 2008 is contained in section 162, which empowers a court to make an order declaring a director delinquent or placing him under probation in specific instances. The effect of section 162 is that a court is empowered to remove a director from the board of directors. The focus of this thesis is the removal of directors from office by the board of directors and by the judiciary. The thesis explores the underpinning philosophy of the statutory provisions relating to the removal of directors from office. It also examines the impact of the power given to the board of directors and to the courts to remove a director from office. The grounds and the procedures for the removal of directors by the board of directors and the judiciary are examined. The fiduciary duties applicable to directors in removing a director from the board of directors are also explored. In addition, this thesis examines the removal of directors holding multiple positions or capacities in relation to a company, such as an employee or a shareholder with loaded voting rights. The remedies which may be relied on by a director who has been removed from office by the board of directors are examined. Recommendations are made to strengthen and improve the provisions in the Companies Act 71 of 2008 relating to the removal of directors from office by the board of directors and the judiciary. Amendments to the Companies Act 71 of 2008 are suggested to remove ambiguities; to guard against the abuse of sections 71(3) and 162; to improve the grounds and procedures for the removal of directors by the board of directors and the judiciary, and to enhance the remedies that may be relied on by a director who has been removed from office by the board of directors.
Keywords: Corporate governance; Directors and shareholders power; Directors of corporations; Fiduciary duties; Investor relations; Removal of directors from office; Stockholders' voting; Voting rights

The directors’ fiduciary duty to act in the best interests of the company: the possible developments of common law by statute and how they affect human rights - Nomadwayi, Bakhulule (University of KwaZulu-Natal, 2018)
This research traces the developments of the directors’ fiduciary duty to act in the best interests of the company and looks at how these developments affect human rights and interests of stakeholders. The main focus of the study is on the human rights impact of this duty. Initially, this duty was only regulated in terms of common law which proved to be problematic. The problem with common law lies within the definition of ‘best interests of the company’, which not only exclude the interests of other stakeholders but also has the potential to bring about violation of human rights, particularly the rights to equality, dignity and fair labour practice. At common law best interests of the company means interests of the company itself and its shareholders. The common law only protects the company and its shareholders, while excluding the rights and interests of stakeholders. The common law duty to in the best interests of the company is not in line with our contemporary law because it ignores human rights. The neglect of human rights by this duty renders it inconsistent with the values contained in the Constitution. Furthermore, the exclusion of stakeholders’ rights by this duty cannot be justified because stakeholders play an important part in safeguarding the stability and continued existence of the companies. The fiduciary duty to act in company’s best interests is now contained in the Companies Act of 2008. Inclusion of this duty in the Act enables our courts to interpret it in a manner that protects human rights and which takes into account interests of other stakeholders. Section 7 (a) of the Act provides that among other goals of the Act is the promotion of compliance with the Bill of Rights when applying the company law. The impact of section 7 is that it imposes an indirect duty on directors to consider the human rights impact of their decisions. Section 158 of the Act enables the courts to “develop common law as it is necessary to improve the realisation and enjoyment of rights established by the Companies Act of 2008.” Given this recognition of the Bill of Rights by the Companies Act, it’s of vital importance that our courts should interpret and apply the duty to act in the best interests of the company in manner that is consistent with the Constitution. Directors are now obliged to pay attention to the human rights impact of their decisions.
Keywords: Best interests of the company; CSR; Corporate Social Responsibility; Fiduciary duty

Corporate governance and resource management in Nigeria: a paradigm shift - Oyewunmi, Olabode Adeleke; Oyewunmi, Adebukola Esther (Business Perspectives, 2018)
The underlying significance of instituting measures for effective corporate governance and rewarding resource management outcomes cannot be relegated. The countries and organizations that deemphasize this practice have mortgaged their potential for long-term growth and corporate sustainability. This paper adopts a critical narrative method to deconstruct the essence of corporate governance and economic resource management ideals. The paper furthers the ongoing conversations on two interrelated business concepts, and provides an apt perspective towards unlocking the essence of corporate governance relative to the Nigeria’s corporate environment. It depicts a corporate paradigm shift that accommodates the dynamics of global best practices taking into account some peculiarities of Nigeria’s corporate climate. The paper also captures relevant theoretical dimensions and pragmatic policy propositions, especially for underperforming socio-economic contexts. In the light of the central theme, specific issues are discussed under the sub-headings of conceptual and theoretical clarifications, corporate governance and resource management in Nigeria, shifting the paradigms, conclusion and recommendations.
Number: 1 http://www.businessperspectives.org
Keywords: Corporate governance; Nigeria; Resource management

Legal framework of Directors' Duties in OHADA Law (Senegal) - Niang, Oumar (International Journal of Business, Economics and Management Works, 2017)
This article is aimed to study the legal framework of directors’ duties in Ohada law. The Organization for the Harmonization of Business Laws (OHADA),is a supranational system of business laws that, as implemented in Senegal is trying to regulate all the core businesses.Ohada displays two level of mixing.Firstly,Ohada Law is supranational, it becomes part of the internal law of each state member but still remains supranational characteristics.Secondly,Ohada being at least partially French-inspired, we can understand that the most of the countries which adopted Ohada Laws are French-speaking. The duties of Directors in Senegal are regulated mainly by the uniform companies’ act which is part of the Ohada law. It should be noted that before the adoption of Ohada, company law was governed by the code of civil obligations and in its fourth part. For companies listed on the RSE, they must comply both with the general regulations of the BRVM and with the provisions of the Uniform Companies Act concerning publicly traded companies. This article aims to illuminate the lanterns on the question of the duties of directors in Ohada law, during my research I have observed that subjects such as corporate governance in general and the duties of directors in Ohada are left stranded by most researchers. This is why this topic has an interest in reabsorbing this gap insofar as the legal framework of the duties of directors often mentions many questions because of the lack of loyalty and diligence of certain directors.
Copyright © 2017 KWP Journals. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. International Journal of Business, Economics and Management Works Kambohwell Publisher Enterprises www.kwpublisher.com
Keywords: Company law; Corporate; Directors Duties; Governance; Senegal

The stakeholder theory of corporate control and the place of ethics in OHADA: The case of Cameroon - Sama-Lang, Irene; Zesung, Njonguo Abel (African Journal of Business Ethics, 2016)
The rapid increase in globalization in the last two and a half decades has caused businesses to easily transcend national boundaries. States respond to such flexibility by harmonising their laws to easily adapt to such changes in order to attract investments. This is the case with the OHADA jurisdiction where its architects foresaw an economic spur through integration of business laws. Though expected to stay within the bounds of the law, the law cannot absolutely determine how businesses should prioritise their stakes. As such, ethics comes in to complement the law. This article uses the stakeholder theory of corporate control to investigate the place of ethics in OHADA, as applied in Cameroon. It concludes that an altruistic social conscience is still highly wanting.
Keywords: Business; Corporate control; Corporate law; Ethics; OHADA; stakeholder

The position of the whistle-blower in South African law - Isparta, Louise Dorothy (University of South Africa, 2014)
The position of the whistle-blower is known to be a precarious one, with the whistle-blower often either regarded as a hero or a reprehensible traitor. Various pieces of legislation have attempted to remedy their precarious position, especially within the employment relationship, and in which the whistle-blower more often than not has the most to lose. The study at hand has the specific objective of comparing the position of the whistle-blower in terms of South African Law, against 16 specific measurables, and in comparison with the position of the whistle-blower in New Zealand, Australia (Victoria) and the United Kingdom. In the main, the protection offered to the whistle-blower within the South African context, is embodied within the Protected Disclosure Act 26 of 2000 (hereinafter referred to as the “PDA”).In examining the protection afforded to the whistle-blower in South Africa, it is concluded that the framework involved extends much further than just the mere provisions in the PDA. However, there are admitted challenges in respect of this framework as discussed, both legislative and non-legislative, especially in respect of duties of disclosures placed on persons in circumstances in which concurrent protection is not afforded to the whistle-blower. With reference to the comparison in respect of the measurement parameters set, it was found that the PIDA (UK) meets the least amount of the measurements set, with the PDA A (Australia, Victoria) meeting the most of the measurements; the PDA NZ is equally balanced in meeting and not meeting the measurements and the PDA meeting less of the measurements than not, but still meeting more than the PIDA. It was found that had it not been for the catch-all provision contained in section 4 (1) (b) of the PDA, the PDA would have ranked last.
Keywords: Disclosure of information; Lanceur d’alerte; Protected Disclosure Act; Protected disclosure; Public Interest Disclosure Act; Whistle blowing; Whistle-blower

Complex ownership structures, banks' capital structure and performance - Zedek, Nadia (Université de Limoges, 2014)
Cette thèse examine l’impact de la structure actionnariale sur la structure du capital et la performance des banques commerciales européennes sur la période 2002-2010. Elle est composée de trois essais empiriques. Le premier chapitre teste l'effet de la divergence entre les droits de contrôle et les droits pécuniaires d'un actionnaire ultime sur l’ajustement du ratio du capital à son niveau optimal et sur l’offre de crédit par les banques. Les résultats montrent qu’en présence de divergence entre les droits de contrôle et les droits pécuniaires, les banques n’émettent pas du capital pour augmenter leur ratio et, au contraire, elles réduisent leur taille en ralentissant leur offre de prêts. Le chapitre 2 teste l’effet de cette divergence sur la rentabilité et le risque bancaires en temps normal et en temps de crise. Les résultats montrent que bien qu'une divergence entre les droits de contrôle et les droits pécuniaires soit associée en temps normal à une rentabilité plus faible et un risque plus élevé elle a, à contrario, amélioré la rentabilité et contribué à la résilience des banques pendant la crise financière de 2007-2008. Le troisième chapitre teste si le réseau des actionnaires auquel la banque est liée au sein d’une chaîne de contrôle affecte la relation entre la diversification et la performance. Les résultats montrent que la présence des investisseurs institutionnels dans les chaînes de contrôle aide les banques à tirer des bénéfices lorsqu’elles diversifient leurs activités.
Keywords: Actionnariat; Banques; Banques européennes; Capital; Capital Structure; European Banking; Ownership; Structure du capital

Human capital disclosure in corporate annual reports - Adelowotan, Michael Olajide (University of South Africa, 2014)
It is generally acknowledged that human capital intangibles are major value drivers in the new economy characterised by information and technology. The main purpose of this study is to examine the extent to which companies listed on the Johannesburg Stock Exchange disclose information on human capital related issues. The study combined both qualitative (literature reviews and content analysis) and quantitative (survey questionnaire) methods to collect data of 60 corporate annual reports (CARs) of listed companies in South Africa from survey questionnaires administered on various categories of preparers and users of these CARs. The study made use of 91 human capital disclosure checklists developed from literature reviews for the purpose of data collection. The data analysis was done with the aid of Atlasti-a qualitative data analysis software and SPSS- a quantitative data analysis software. The findings show that majority of the items on the disclosure checklist are not yet disclosed in the CARs even though most of the items on the checklist are adjudged to be useful for organisational value creation. In view of the initial findings of this study, a human capital disclosure framework is recommended.
Keywords: Annual report; Corporation reports; Discretionary disclosures; Human capital; Human capital disclosure framework; Intangible assets; Intangible property; Intellectual capital; Mandatory disclosures; Personnel management

Chapter 4 offer regulation under the 2008 Companies Act - Labuschagne, Frederik J. (University of Pretoria, 2014)
Chapter 4 of the Companies Act of 2008 aims to regulate offers to the public of securities and is reviewed against the principles which underscore the regulation of offerings. An overview of the historical development of the company which is parallel to the regulation of securities shows the crystallized principles which are compared against the development and enactment of the current regulatory regime. The concept of “complete law” as key element to effective regulation is discussed and applied in the review of Chapter 4 determining the effectiveness of the dispensation. The three determining concepts of regulation: the “offer,” “securities” and “public” are studied against the definitions which determine regulation and the inclusion of secondary market regulation of unlisted securities. Serious shortcomings in the process are identified. These errors, together with the practical problems of defining and regulating the secondary market in Chapter 4 read with the remainder of the delineating definitions, concludes that the current system is not in line with the principles of regulation and the Grundnorm of fraud prevention, resulting in Chapter 4 falling under the concept of “incomplete law” resulting in a high probability of enforcement failure and inefficiency. A comparative overview related to the jurisdictions of the United Kingdom and the United States follows with recommendations aimed at amending Chapter 4 relating to the regulatory regime in toto as well as the regulation of unlisted securities in the secondary market.
URI: https://repository.up.ac.za/handle/2263/45981
Keywords: Companies Act; Offer regulation

The requirement of consent for the transfer of shares and freedoms of movement : toward the liberalization of private limited liability companies : a comparative study of the laws of Portugal, France, Italy, Spain, the United Kingdom and the United States and its interplay with EU law - Vicente, Lécia (European University Institute, 2014)
Toward the Liberalization of Private Limited Companies – A comparative study of the laws of Portugal, France, Italy, Spain, the United Kingdom and the United States and its interplay with EU law’, I try to shed light on the dynamics of private limited liability companies (PLLCs), and how they can be legally designed to become efficient units of economic development in Europe and the United States. I take a social sciences approach to the legal question: How does the design of clauses establishing restrictions on transfer of shares of private limited liability companies affect investment made in these companies and their consequent development? To answer this question, I develop two parallel lines of investigation. First, I undertake an embedded historical study to trace the evolutionary patterns of PLLCs in six countries. Furthermore, I longitudinally track the standards of behavior of market agents in the selected jurisdictions. Second, I develop my legal research by looking at an anomaly regarding the transfer of shares and changes in the ownership structure of these business organizations. Transfer of shares in PLLCs is, for the most part, regulated by default rules which impose restrictions on transfers. Typically, the parties do not contract around these default rules. The anomaly lies in the fact that, even though shareholders of these companies do not opt out of these rules, shareholders often ignore them and/or breach them at a later stage.
Keywords: Business enterprises; Corporate law; Limited liability; Private companies

Corporate governance in Kenya's state corporations: A critique on the appointment and dismissal of directors of boards of state corporations - Kamau, A. G. N. (University of Nairobi, 2013)
This study interrogates corporate governance practices within Kenya’s State Corporations with particular reference to the appointment and dismissal of directors of the Boards of these corporations. It recognizes that these directors are the anchors for the implementation of corporate governance practices in these corporations. The appointment and dismissal of these directors have been based on, inter alia, political considerations kinship, patronage, ethnicity and other non objective criteria other than merit. This has often impacted negatively on the performance of these corporations. This study traces the evolution of corporate governance generally, documents it’s historical development in Kenya and examines the current practices on the appointment and dismissal of directors of boards of state corporations. The data collected targeted a majority of State Corporations which demonstrates that past criteria for Directors recruitment and their dismissal was based on non objective criteria. The study is instructive on the fact that though best practice and corporate governance principles have not been fully embraced in the appointment and dismissal of Directors of Boards of State Corporations there is a positive move towards the adoption of these principles in such appointments and dismissals. The impetus for this was the promulgation of the Kenya constitution 2010 which is itself a good corporate governance document.

Three Essays on Bank Lending and Corporate Finance - Chen, Liqiang (McMaster University, 2013)
This thesis includes three essays on several important topics in empirical finance: Chief Executive Officer (CEO) risk-taking incentives, the cost and syndicate structure of bank loans and corporate investments with internal funds. This thesis contributes to these aspects of finance literature and the three essays are presented in Chapter 2, 3 and 4. The first essay investigates how implicit contractual relationship between creditors and borrowers attenuates the conflict of interest between creditors and shareholders that arises from CEO compensation contracts when a corporation can be considered a nexus of explicit and implicit contractual relationships among stakeholders. We find that bank loans for firms with CEOs who are provided with risk-taking incentives have higher spreads and shorter maturities. A relationship between the lender and its borrower mitigates the influence of incentives for CEO risk-taking on loan spread and loan maturity. Such a relationship is especially beneficial for informationally opaque firms. The results are robust to the endogeneity of relationships and the simultaneous determination of loan spread, loan maturity and collateral requirements. Our results highlight the importance of the interaction between explicit and implicit contractual relationships to a firm’s borrowing cost. The second essay investigates the effects of a borrowing firm’s CEO risk-taking incentives on the structure of the firm’s syndicated loans. The conflict of interest between creditors and shareholders arising from CEO risk-taking incentives is a major concern of borrower moral hazard for syndicate lenders, which require intensive monitoring by lead arrangers in a syndicate. When CEO risk-taking incentives are high, syndicates are structured to facilitate better due diligence and monitoring efforts. These syndicates have a smaller number of total lenders and are more concentrated, and lead arrangers will retain a greater portion of the loan. Moreover, we examine the factors that affect the link between CEO risk-taking incentives and syndicate loan structure. CEO risk-taking incentives have a lesser effect on the syndicate structure when lead arrangers have a good reputation and have a prior lending relationship with a borrowing firm. By contrast, CEO risk-taking incentives have a greater influence on syndicate structure when borrowing firms are informationally opaque, are financially distressed or have low growth prospects. The third essay studies corporate investments with internal funds when firms face real investment friction using a sample of U.S. oil companies from 2003 to 2011 before and after the 2008 financial crisis. We show that firms’ capital expenditures are more sensitive to their lagged cash holdings than to their contemporaneous cash flows. By making investments with realized cash holdings, firms can avoid the investment adjustment costs that are incurred when investing with uncertain cash flows. We also show that cash flow policies are affected by liquidity constraints following the 2008 financial crisis: firms build up more cash reserves from cash flows, cut back payouts and raise more debt to maintain cash holdings.
Keywords: Bank lending; Cash flows; Cash holdings; Corporate Finance; Executive compensation; Financial Management; Investments; Managerial incentives

Entrepreneurial financing decisions, venture capital ownership and bargaining power - Heughebaert, Andy (Ghent University, 2013)
It is widely acknowledged that entrepreneurial companies play a key role in shaping a local economy. Entrepreneurial companies are a source of growth and innovation for an industry and provide jobs for the local population. However, entrepreneurs of high growth oriented companies rarely have the capital to finance their innovative ideas themselves and therefore also have to accept the risks associated with assessing and acquiring the necessary finance resources from other investors. The goal of this dissertation is to study the impact of venture capital (VC) finance on such entrepreneurial finance decisions. Although VC investors are a highly focused and specialized kind of investors that offer a wide range of differentiated services, it is to date still unclear how VC investors may reduce agency costs for other potential investors. The first study of this dissertation studies the effect of VC finance and associated VC ownership for finance decisions from other investors who have the potential to invest in these companies. This study demonstrates that VC ownership results into a larger supply of finance for the entrepreneurial company. Second, I find that VC ownership results into an even larger positive effect on capital investment decisions from equity investors as VC finance is typically also associated with the implementation of an equity-oriented corporate governance mechanism in entrepreneurial companies. VC ownership does not have an effect on the supply of finance from financial debt investors, however. Nevertheless, I find that debt finance is equally available for companies with VC ownership as compared to companies without VC ownership, which is a surprising result given the high risk associated with high growth companies that raise VC finance. Another important finding of this study is that the positive effect of VC ownership is stronger for repeated VC finance versus non-repeated VC finance. In fact, these results indicate that the effect of VC finance for entrepreneurial companies’ finance decisions is considerably larger if VC investors commit to further finance the company. The second study of this dissertation extends the first study and explores the effect of VC ownership on entrepreneurial finance decisions in different institutional settings. Although the effect of VC ownership is not limited to one specific institutional context, this study shows that its impact on entrepreneurial finance decisions is stronger in countries with a better quality of law enforcement and in countries where the entrepreneur is able to obtain a fresh start after bankruptcy. Specifically, in countries with a better enforcement of law, VC investors are more effective in reducing agency problems between entrepreneurs and potential investors. The attractiveness of a fresh start after bankruptcy will also be higher for an entrepreneur who raised VC finance, as VC investors focus more on maximizing the value of their portfolio rather than on the survival of individual firms. The third study acknowledges the fact that VC investors are not all equal and explores which VC investor types have more bargaining power versus the entrepreneur and how such differences in VC investor bargaining power affect company valuations in VC investment rounds. VC investor bargaining power is important because company valuations are the outcome of negotiations between the VC investor and the entrepreneur. We show that university VC firms and government VC firms negotiate lower valuations compared with independent VC firms. The proprietary deal flow of university VC firms and the limited competition in niche markets in which government VC firms compete will directly increase their bargaining power versus the entrepreneur, which these VC investor types then further exploit by negotiating lower company valuations compared with independent VC investors. Although differences in VC investor type did not affect entrepreneurial finance decisions in the first and second study, they do affect the equity stake that an entrepreneur will have to give up in order to raise VC finance and in order to a have a greater access to entrepreneurial finance from potential investors in the future.
http://hdl.handle.net/1854/LU-4096609
Keywords: Bargaining power; Financing decision; Venture capital

Corporate Restructurings in Zimbabwe : a Legal Analysis of the Regulation of Corporate Mergers and Acquisitions in Zimbabwe - Nzero, Ignatious (University of Pretoria, 2013)
The Zimbabwean economy rapidly declined over the past two decades. A record hyperinflationary environment and a collapse of the financial service sector coupled by lack of external lines of credit created a difficult operating environment for corporate businesses. Businesses thus either closed down operations or resorted to survival strategies. Corporate mergers and acquisitions emerged as natural favoured strategies in implementing survival corporate restructuring transactions. However, the success of such strategies largely depends on the effectiveness of the merger regulatory framework, that is, its ability to promote beneficial corporate restructuring transactions on one hand and to maintain the competitive structure of the market on the other hand. This research analyses the current merger regulatory framework in Zimbabwe and assesses whether it is suited to promote beneficial corporate restructuring transactions implemented through mergers and acquisitions without unnecessarily distorting the competitive structure of the market. Employing the failing firm doctrine as the focal point, the research identified a number of shortcomings within the current merger regulatory framework that impacts upon its ability to effectively promote beneficial corporate mergers and acquisitions without sacrificing the competitive market structure. Selected comparative jurisdictions were used to draw various lessons for Zimbabwe. The aim of the comparative study was not to provide an exhaustive analysis of these jurisdictions but to identify specific arrears that can be used to develop and suggest an effective merger regulatory framework for Zimbabwe. In order to remedy the identified shortcomings inherent within the current Zimbabwean merger regulatory framework, this thesis proposes a number of amendments to the current Competition Act [Chapter 7:01] of 1996. These proposed amendments are aimed at bringing clarity, flexibility and strengthening the merger regulatory framework including the institutions tasked with such. The research is primarily a legal analysis of the Zimbabwean merger regulating statute and its implications on any decisions made by the competition authority. As such, the thesis states the status of legal development in Zimbabwe and the selected comparative jurisdictions as of 31 July 2013.
URI: https://repository.up.ac.za/handle/2263/53211

Board Structure, Ownership Concentration and Intellectual Capital - Zhang, Meiyi (Victoria University of Wellington, 2012)
This thesis investigates the influence of board structure and ownership concentration on the level and value relevance of intellectual capital disclosure. This thesis is motivated by the limited post-IFRSs (International Financial Reporting Standards) adoption intellectual capital disclosure studies carried out in a less stringent regulatory environment of New Zealand, and limited research addressing the determinants of the level and value relevance of intellectual capital disclosure. Based on an application of agency theory, cost-benefit theory and value relevance approach, this thesis argues that firm-specific factors are expected to have a significant impact on the level and value relevance of intellectual capital disclosure. Within the agency theory, board structure and ownership concentration mitigate agency costs by enhancing the monitoring function of the board over managers’ opportunistic behaviour, which consequently influence the level of intellectual capital disclosure. In addition, as New Zealand has less tough rules in relation to board structure and ownership concentration, it is expected that these relationships will be more easily identified in the New Zealand context. Second, as most of the intellectual capital disclosure is voluntary, this disclosure is subject to a firm’s cost-benefit analysis. Cost-benefit theory suggests that a firm should not fully disclose its information unless the benefits outweigh the costs of the disclosure. Therefore, the level of intellectual capital disclosure is also influenced by the factors that determine the costs and benefits of the disclosure. Finally, this thesis adopts the value relevance approach to measure the quality of the disclosure. It is expected that the factorsassociated with the level of the disclosure also influence the value relevance of the intellectual capital disclosure. This thesis is based on a sample of 155 firms listed on the New Zealand Exchange covering a total of 519 firm-years over the period between 1 January 2008 and 31 August 2011. A self-developed disclosure index and multiple regression analysis are employed to test the hypothesised relationships. Overall, the results indicate that the average level of intellectual capital disclosed by New Zealand listed firms is low and the human capital component is the most frequently disclosed intellectual capital component. The results provide strong evidence that board structure characteristics, including board size and independence, have a significant positive impact on the level of intellectual capital disclosure. There is strong evidence for a non-linear relationship between ownership concentration and the level of intellectual capital disclosure, which is robust to various types of intellectual capital (i.e. human, relational and structural capital). The results show marginal evidence that board gender diversity has a positive impact on the level of intellectual capital disclosure. In terms of the value relevance of intellectual capital disclosure, only board size has a positive impact on the value relevance of the intellectual capital disclosure. In the individual component analysis, board independence is found to have a significant positive impact on the value relevance of the human and relational capital disclosures. This thesis provides the most recent evidence on the influence of board structure and ownership concentration on the level and value relevance of intellectual capital disclosure in a less stringent regulatory environment of New Zealand. These findings have important implications to regulators, and assist information users in the interpretation of the voluntary intellectual capital disclosure.

The external relations of company groups in South African law : a critical comparative analysis - Stevens, Richard Arno (University of Stellenbosch, 2011)
Groups of companies are part of the realities of the modern economic system. Despite the fact that such groups often function as a single economic entity, the legal point of departure remains that each company within the group of companies is a separate juristic person. The result of this is that a creditor of a company within the group can, in principle, only enforce his claim against the company which he contracted with or which caused him harm. Should he wish to claim from the holding company or other solvent companies within the group, he would have to rely on an exception to the doctrine of separate juristic personality, viz the possibility of piercing the socalled corporate veil. This dissertation is a comparative study of the extent to which the law protects a creditor of an insolvent company within a group. The applicable laws of Australia, Germany, New Zealand, the United Kingdom and the United States of America, were investigated and compared to the South African position. The dissertation concludes that the South African legal treatment of the problem is unsatisfactory and that the law should be amended through appropriate legislation.
URI: http://hdl.handle.net/10019.1/6883
Keywords: Company groups; Creditors; South African companies; South African law

Reforming corporate governance: Protecting minority shareholder rights through a strong corporate law system - Deniz, Ozden (American University, 2010)
Keywords: Association law; Corporate governance; Corporate law; Minority shareholder (protection)

Executive Remuneration as an Aspect of Corporate Governance under OHADA's Corporate System - Kelong, Richard William Ngwa (MPRA Paper, 2009)
With growing importance attached to the notion of executive remuneration, OHADA’s policy makers have also considered the concept as a fundamental element in any corporate governance system. In this regard, they have put in place a policy framework that regulates executive remuneration within OHADA’s corporate system to ensure that executive benefits are appropriate and lawful to enable directors remain objective in respect of their fiduciary duties towards the company. This paper discusses executive remuneration as an aspect of corporate governance under OHADA's corporate system. In doing so, the paper describes the executive remuneration policy under OHADA's corporate system and makes an appraisal of the abovementioned policy with the goal of stating its potential and limitation as well as proposing a reform that will guarantee its effectiveness as a mechanism in ensuring good corporate governance.

On formation of a share company in Ethiopia - Tesfay, Seyoum Yohannes (Journal of Ethiopian Law, 2008)
Keywords: Attributes; Ethiopian law; Formation; Share company

Recognition of various stakeholder interests in company management - Esser, Irene-Marié (University of South Africa, 2008)
Good corporate governance should be the cornerstone of all company management. Directors ought to know in whose interests the company should be managed. This thesis attempts to answer the following question: whose interests must be granted primacy in the management of a company? In chapter 1 it is stated that shareholders' interests are traditionally granted primacy in the management of a company. There has, however, been a shift in public opinion towards recognition of a wider variety of interests that should be considered than only those of the shareholders. These interests include, inter alia, environmental interests and those of the investors, employees and consumers. This thesis thus focuses on the primary stakeholders, namely individual shareholders, creditors, employees, consumers and suppliers. In chapter 2 a theoretical foundation is provided on the nature of a company. The different theories on the nature of a company, emphasising either shareholder primacy or stakeholder protection, are discussed. A combined new theory is proposed. It is suggested that the confusion relating to the meaning of "the company" needs to be eliminated. Chapters 3, 4 and 5 provide an international comparison of the company law in Botswana, Australia, New Zealand and the United Kingdom. The focus falls, firstly, on directors' duties, secondly, on the question in whose interests directors should manage a company and, thirdly, on the codification of their duties. In chapter 6 the South African position is evaluated. First, the possible stakeholders are identified and the protection currently afforded them is explained. The reports of the King Committee on Corporate Governance, the Policy Document on company law reform as well as the Companies Bill of 2007 are discussed. Draft clauses are recommended to be incorporated in new company legislation to provide directors with clarity on what is expected of them. It is the aim of this thesis to provide clarity on whose interests should receive primacy when directors manage a company. The outcome of this research should provide a clear indication to South African directors of what is expected of them and who the beneficiaries of their fiduciary duties are.
Keywords: Codes of best practice; Consumers; Corporate governance; Corporation law; Creditors; Directors' Duties; Shareholder value; Shareholders; Social responsibility of business; Stakeholders

Directors’ duties to creditors - Lombard, Sulette (University of Pretoria, 2007)
Creditors of the corporate business form are in a vulnerable position. Recognition of the plight of corporate creditors led to the implementation of various legal measures aimed at protecting their financial interest in the company. These measures proved disappointingly inadequate in many instances. As a result the judiciary in some jurisdictions felt compelled to develop existing legal principles pertaining to directors’ duties in such a way that they could be used to facilitate protection of corporate creditors’ interests. This development did not meet with universal approval. Those opposed to the extension of directors’ duties to protect creditors’ interests have three main arguments against it. The first is related to conceptual issues and policy concerns. The second argument is that existing remedies are more than adequate to protect creditors’ interests. A last argument against a directorial duty to creditors pertains to the practical implementation of this extended duty. It is argued that the existing legal framework with regard to directors’ duties is not suitable to provide protection for creditors’ interests. However, it was shown in this study that the extension of directors’ duties to protect creditors’ interests is indeed justifiable on a sound conceptual basis and that policy concerns regarding such an extension are either unfounded, or should be addressed in some other way. An analysis of existing protective measures and remedies often referred to by opponents of an extension of directors’ duties, namely statutory personal liability of directors, traditional insolvency remedies, and the piercing of the veil doctrine furthermore showed that these measures are inadequate. This leads to the conclusion that there is a definite need for an alternative remedy, such as the extension of directors’ duties to include creditors’ interests. The existing legal framework in respect of directors’ duties furthermore proved to be capable of being successfully adapted to include creditors’ interests. Central issues in this respect, as was indicated by an analysis of case law, are the point in time when the duty to creditors is triggered, the beneficiary of the duty, in other words who would have locus standi in case of a breach of the duty, and the type of protection afforded to creditors’ interests by way of fiduciary duties and the duty of care and skill. The existing legal framework also provides measures in terms of which honest and diligent directors may be relieved from liability, such as indemnification, relief granted by the courts and director liability insurance. These measures, if formulated correctly, may achieve and maintain the essential balance between accountability and entrepreneurial freedom. The legislature appears to have adopted a cautious approach to the issue of directors’ duties to creditors. It thus seems to be up to the judiciary to develop directors’ duties to creditors in a meaningful way. Pioneering in this respect has already been done in Australia, New Zealand, England, Canada and the United States of America. It is to be hoped that the South African judiciary will follow suit when the opportunity to do so arises.
Keywords: Beneficiary of directors’ duties; Company law; Company’s interests; Corporate law

Legal aspects of corporate governance in the republic of South Africa: towards a possible model for improved stakeholder relations within the corporation - Spisto, Michael Paolo (University of the Witwatersrand, 2007)
Traditionally, company law assumes that the directors’ role is to run the company for the benefit of its shareholders alone and to maximise profits for them. It can be argued, however, that this view is too narrow and outdated; that is, company directors should have regard to the rights and interests of a broader range of corporate stakeholders. Hence, the question is whether we should change our perception of the company or corporation from one run by directors dedicated exclusively to serving the interests of shareholders to that of a corporation whose main purpose is to bring benefit not only to its owners and creditors, but also to its employees, the community and the environment. Given that reforms of directors’ duties in light of the above considerations have found their way into legislation across the globe, this thesis examines how and to what extent legal rules and policies should develop in South Africa to place directors under a positive duty to take account of the interests of bodies other than shareholders. Current South African company law does not contain clear rules regarding corporate governance issues and the duties and liabilities of directors. These matters have been left to the common law and Codes of Corporate Practice. Thus, there is no extensive statutory scheme in South Africa, which covers the duties, obligations and accountability of directors. The focus in this thesis is on the rights and interests of employees and the premise that is defended is that it is valuable to corporations to provide employees with an institutionalised voice at board level. It is argued that there is global evidence that where employees participate in the decision-making processes of the company, performance is generally enhanced. This, in turn, directly impacts upon and improves economic productivity, generating a ‘win-win’ situation. The question of the duties of company directors and managers is attracting much attention in South Africa. With rapidly developing and changing labour legislation in South Africa, it is essential to consider the extent to which the country should reassess its traditional principles of company law and corporate governance policies in order to encourage participatory roles for employees in the workplace. It is argued that if South Africa is to improve corporate productivity levels with its re-entry into international markets, management and labour must find improved ways of dealing with one another. The main purpose of this thesis, therefore, is to propose and formulate a workable corporate governance model for South Africa – one that would be advantageous to all stakeholders, especially the employees. This is achieved by comparing and contrasting international models of corporate governance and by applying the best features of each to the unique South African corporate system of values, structures and traditions. It is suggested that the current unitary board structure operating in South Africa has become outdated and does not provide employees with rights enabling them to engage in the decision-making processes of the corporation with their employees at an adequate level. In its place, a two-tier board system of corporate governance is proposed. The economic success of a company will bring about social benefits to many stakeholder constituencies. This will not happen if the company is a financial failure. The issue of obliging directors to act primarily for the benefit of shareholders alone is questioned. Corporate governance reforms were undertaken in many parts of the world in the late 1980’s and early 1990’s. This reform process questioned whether the interests of the company should be managed for the shareholders alone or for the other corporate stakeholders as well. There are many views that strongly support the idea that corporate governance should be seen as a system by which corporations are to be governed for the benefits of all stakeholders, including shareholders, employees, creditors, suppliers and the community. In this way, companies should be run as communities in partnerships with all their stakeholders. Thus, this thesis proposes that the success of a company is inextricably intertwined with a consideration of the rights and interests of its employees and other stakeholders.
URI: http://hdl.handle.net/10539/1969
Keywords: Bond/Debenture Holders; Community; Companies; Corporate governance; Corporations; Creditors; Employees; Environment; Interests; Models; Rights; Shareholders; South Africa; Stakeholder Relations

Corporate governance: a practical and effective response to the challenges raised - Fridman, Josef J. (McGill University, 2004)
This thesis seeks to address corporate governance from both a practical as well as an academic perspective. It searches for solutions to self-interest and agency costs, problems that it is posited are innate to the anthropomorphism of the corporation and to the separation of management and ownership of widely held, publicly traded, corporations. Practically, this dissertation is anchored in experience, garnered from empirical research, based on in depth and general surveys, as well as detailed interviews. It examines the workings of corporations, including their boards of directors, of gatekeepers, of checks and balances and of shareholders and the relative importance and rationale for the roles that they play. Based on the academic and empirical efforts it is posited that self-interest and the funneling syndrome, (a process whereby information required for decision making is constrained and managed by those in control), almost always predetermines the outcome of the corporate formal decision making process involving the board of directors. This facilitates abuse. When it occurs and there appears to be no accountability, confidence essential to the capital markets, quite understandably, suffers. A hypothesis is advanced to explain the complexity of a potential failure of corporate governance through a relatively simple formula. It draws conclusions as to what is required to help address the challenges raised by the breakdown in effective corporate governance and to help instill greater investor confidence. A self-assessment mechanism to help quantify how effectively a corporation is dealing with corporate governance, both on an absolute basis (comparing itself year over year) and on a relative basis (compared to one's peers) is proffered. This tool of more effective corporate governance, seeks to identify the causes for breakdowns in corporate governance and to assist a board of directors in dealing more proactively with this challenge.
https://escholarship.mcgill.ca/concern/theses/nz8060241
Keywords: Corporate governance

Community competence to control mergers : the jurisdictional divide - Burnley, Richard (European University Institute, 2002)
Keywords: Antitrust law; European Union countries; Unfair Competition

Globalization and the limits of National merger control laws: gaps in global governance and the need for an international merger control regime - Wilson, Joseph (McGill University, 2002)
From an economic perspective, globalization is dismantling national barriers to entry and is transforming domestic markets into a global market. To meet the challenges posed by the integration of markets, corporations are joining forces with their former competitors to expand their presence in the global market. Rapid growth in transnational mergers to create global corporations is one of the key features of globalization. As multinational corporations are uniting, so should antitrust agencies that regulate them. Antitrust agencies around the world are realizing that the consumers whom they are mandated to protect are being adversely affected by decisions made beyond their national borders. By using the "effects" test, countries bring within their jurisdiction review of any merger or acquisition involving foreign companies with significant revenue or assets within their jurisdiction. The proliferation of merger control laws, in the absence of a mechanism to coordinate the transnational merger review, places an unnecessary burden on merging parties, and runs the risk of divergent outcomes, which at times cause friction among nation-states. Both to alleviate unnecessary burdens imposed on corporations and to reduce inefficiencies produced by the disparate review of a single transnational merger by several countries, this thesis proposes an International Merger Control Regime integrated into the WTO. The proposal focuses on ways to operationalize a "Lead Jurisdiction" model of oversight rather than on the creation of a new supranational decision-making agency. WTO dispute settlement and arbitration would be used to resolve conflicts arising out of the inability of a Lead Jurisdiction to arrive at an outcome satisfactory to other significantly affected jurisdictions.
Identifier: https://escholarship.mcgill.ca/concern/theses/2z10wr888
Keywords: International merger control; Merger; Merger control